Kualitas Pelayanan Publik Di Kantor Camat Pineleng Kabupaten Minahasa - Tombiling, Nikita Debora; RUMAPEA, PATAR; OGOTAN, MARTHA (Sam Ratulangi University, 2017)
ABSTRAK: Public Service is any activity in the framework of fulfillment of basic needs in accordance withthe basic rights of every citizen or resident of an item, service and administrative service provided by theservice providers related to the public interest. Examples of public services in the form of administrativeservices namely the making of Domicile Letters, Birth Certificates, and Purchase Deed Certificate, servicesin the form of services such as post office and bank. While services in the form of goods such as tax paymentsused for the construction of state infrastructure such as bridges and highways. Quality of service is acondition where created a dynamic relationship between users and service providers, good service, human.Public service is closely related to the ability, responsiveness, timeliness, and available infrastructure. If theservices provided are in accordance with the expected by service users, it can be said that service is a qualityservice. Conversely, if the services provided are not in accordance with the expectations of service users, itcan be said that the service is not qualified. Good service quality is not based on the perspective or perceptionof service providers but rather based on consumer perceptions and rules or provisions about the quality ofservice.Kata kunci: Quality, Public Service, sub-District Government